Acción Sinérgica de levadura (Saccharomyce cerevisiae) y flavonoides extraídos de la cascara del cacao (Theobroma cacao. L) como mecanismo de inhibición de crecimiento de Listeria monocytogenes - Amaiquema Carrillo, Aurelio Esteban (2025)
This research aimed to evaluate the synergistic action between Saccharomyces cerevisiae and flavonoids extracts obtained from the exocarp of cocoa (Theobroma cacao. L), with the purpose of inhibiting the growth of Listeria monocytogenes under controlled laboratory conditions using a 3x3 experimental design with three repetitions for each treatment. The methodology involved processes dehydration, enzymatic inactivation and grinding of the cacao peles to obtain a pure extract. The extraction process was carried out through a maceration using a solvent with acetona (60%) and wáter (40%). This extract was used for the quantification of total flavonoids by UV-VIS spectrophotometry. In parallel, microbiological tests were conducted to evaluate the inhibition of Listeria monocytogenes using the agar diffusion technique, observing inhibitions halos that depended on the concentrations of yeast and flavonoids. Statistical analysis of the results was performed using Anova and Tukey`s test, which revealed significant differences that confirmed the combination of both compounds has antimicrobial effects. Furthermore, it was observed that the inhibition halos at lower concentrations (400 µg/ml and 10^4 CFU/ml) were smaller, whereas the highest concentration (800 µg/ml and 10^6 CFU/ml) produced larger halos. These findings indicate that the synergy between cacao flavonoids and Saccharomyces cerevisiae may serve as a natural alternative for the control of Listeria monocytogenes in processed foods.